Perfil bioquímico e qualidade de oócito de primíparas Bos indicus submetidas ao protocolo de sincronização da ovulação - Bottino, Miguel Pizzolante (2019)
Currently, timed artificial insemination (TAI) is well established and can be routinely applied in reproductive programs. TAI protocols have been developed to promote control of luteal and follicular functions, which results in satisfactory conception rates. Some limitations in the use of TAI are known and may cause reduction in economic return of the activity. One of these limitations is the use of estradiol/progesterone protocols in primiparous Bos indicus cows. In this category, part of the energy available from the diet or adipose tissue, in addition of being used for milk production and basic maintenance of the animal, is also directed to maintain body growth. Thus, the effects of nutritional deficiencies on reproduction of primiparous cows are more pronounced than in multiparous cows. Despite this knowledge, there is still no detailed evaluation in the literature of factors that may negatively affect the reproduction of Bos indicus primiparous cows. Moreover, such effects have not yet been verified on oocyte and follicular cell quality. Due to the annual renewal of 15 to 25% of the herd with heifers, a considerable percentage of females in the herd are primiparous cows with low reproductive efficiency. Thus, it is important to establish what are the determining factors for low fertility in this category so that we can design studies capable of proposing solutions to these problems.